Effort To Increase Interest And Learning Outcome Of Disc Throwing By Using Melamine Plate Media - Yarmani Yarmani; Yahya Eko Nopiyanto; Habib Noprizal (UNIB Press, 2021)
Efforts to Increase Interest and Learning Outcomes of Throwing Discs Using Melamine Plate Media for Class VIII Students of SMP Negeri 11 Bengkulu Tengah. This study aims to improve the teaching and learning process at SMPN 11 Bengkulu Tengah. CAR was carried out in class VIII.C students, totaling 23 students, consisting of 10 female students and 13 male students. Data collection in this activity was carried out by means of observation sheets, questionnaires and instruments for assessing student movement skills. Observations of teacher and student activities were carried out by two partner teachers in each cycle. Assessment of student movement skills is carried out in each cycle. The results showed that the learning outcomes of students throwing discs using plastic plate media could improve student learning outcomes with learning completeness in cycle I 43% and cycle II 83%. Learning to throw discs using melamine plate media also increases students' interest in learning as shown from the results of the questionnaire, namely from 83% in cycle one to 100% in cycle two which responds positively to learning to throw discs using melamine plate media